Using pulse-shape information for reconstructing cosmic-ray air showers and validating antenna responses with LOFAR and SKA - Karastathis, Nikolaos; Buitink, S.; Corstanje, A.; Desmet, M.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; Jhansi, V. B.; Krampah, G. K.; Mitra, P.; Mulrey, K.; et al. (Proceedings of Science, 2024)
The Low Frequency Array (LOFAR) is capable of measuring extensive air showers through their radio emission in the frequency range of 30–80 MHz, while the Square Kilometer Array (SKA) will be able to expand this range to 50–350 MHz. A very important characteristic of cosmic rays is the mass of the primary particle, which is associated with the atmospheric depth of the shower maximum (Xmax). The standard Xmax reconstruction procedure with LOFAR involves the use of a library of CORSIKA/CoREAS simulations for a specific measured event and uses the energy deposited to the ground in terms of radio fluence. In this study, to extract information about shower development, not only the energy fluence is considered but the possibility of using information from the pulse shape is investigated in both frequency ranges (30–80 MHz and 50–350 MHz). The study of the pulse shape through the pulse agreement of measured data and simulations also provides a way to diagnose the proper functioning of individual LOFAR dipoles.
CRIS-Team Scopus Importer:2025-02-04